2023
DOI: 10.1117/1.apn.2.1.016010
|View full text |Cite
|
Sign up to set email alerts
|

Deep-learning-assisted inverse design of dual-spin/frequency metasurface for quad-channel off-axis vortices multiplexing

Abstract: Recently, the metasurfaces for independently controlling the wavefront and amplitude of two orthogonal circularly polarized electromagnetic (EM) waves have been demonstrated to open a way toward spin-multiplexing compact metadevices. However, these metasurfaces are mostly restricted to a single operation frequency band. The main challenge to achieving multiple frequency manipulations stems from the complicated and time-consuming design caused by multifrequency cross talk. To solve this problem, we propose a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…Moreover, it is confirmed that broadband performance is maintained from 6.79 to 11.33 GHz, with a fractional bandwidth of for oblique incidences up to the angle of with both the TE and TM polarizations. Although the absorbing bandwidth for the incident angle is confirmed as the widest one by comparing it with those of the other chip resistor based metasurface absorber [ 25 , 26 , 27 ], there is still room for improvement by adopting the design strategy utilizing the deep-learning algorithm [ 40 , 41 ] which may enable the optimization of not only the copper pattern, but also the locations of the chip resistors at once. The metasurface absorber composed of optimal copper tiles soldered with chip resistors has a great merit in that they can be easily fabricated with electronic circuits.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is confirmed that broadband performance is maintained from 6.79 to 11.33 GHz, with a fractional bandwidth of for oblique incidences up to the angle of with both the TE and TM polarizations. Although the absorbing bandwidth for the incident angle is confirmed as the widest one by comparing it with those of the other chip resistor based metasurface absorber [ 25 , 26 , 27 ], there is still room for improvement by adopting the design strategy utilizing the deep-learning algorithm [ 40 , 41 ] which may enable the optimization of not only the copper pattern, but also the locations of the chip resistors at once. The metasurface absorber composed of optimal copper tiles soldered with chip resistors has a great merit in that they can be easily fabricated with electronic circuits.…”
Section: Discussionmentioning
confidence: 99%
“…These advantages are helpful for promoting the development of a miniature SPI system using free-space optical components 12 , 31 , 32 , 59 as well as chip-scale integration with silicon photonic circuits 64 or metasurfaces 65 72 …”
Section: Discussionmentioning
confidence: 99%
“…These advantages are helpful for promoting the development of a miniature SPI system using free-space optical components 12,31,32,59 as well as chip-scale integration with silicon photonic circuits 64 or metasurfaces. [65][66][67][68][69][70][71][72] Fig. 13 Acceleration strategy of the DIP-SP processing the images of all spectral bands one by one.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] In addition, some inspiring research focused on intelligent methods for designing metasurface vortex wave generators and other functional metasurfaces. [31][32][33] These advancements have the potential to drive the evolution of metasurfacebased systems toward greater intelligence and functionality.…”
Section: Introductionmentioning
confidence: 99%